A Global Bibliometric Analysis of Consumer Susceptibility to Interpersonal Influence Research: Trends, Themes, and Intellectual Structure (1992–2025) - Audita Sarashanty Aisha; Tony Wijaya (International Journal of Management Science and Information Technology, 2026)
The increasing influence of digital platforms and social media on consumer decision-making has intensified academic interest in Consumer Susceptibility to Interpersonal Influence (CSII), making a comprehensive bibliometric review increasingly important. This study aims to examine the global development of CSII research over the period 1992–2025 using a bibliometric approach. Data were collected from the Scopus database, resulting in a final dataset of 56 relevant documents. The analysis was conducted using VOSviewer version 1.6.20 through four stages: descriptive publication analysis, keyword co-occurrence network analysis, overlay visualization, and density mapping. The findings reveal a fluctuating yet evolving publication trend, with a significant increase after 2010, a peak in 2015, and renewed growth between 2021 and 2023, reflecting the growing importance of social influence in digital consumer environments. The co-occurrence analysis identified seven major research clusters, including consumer behavior and social values, attitudes and product evaluation, interpersonal sensitivity and cultural differences, group influence and purchase intention, emotional and generational factors, sustainable consumption, and digital decision-making. These findings indicate that CSII has evolved from a traditional psychological construct into a multidimensional framework integrating social, cultural, and technological dimensions in understanding consumer behavior. This study contributes to the literature by providing a comprehensive mapping of the intellectual structure and thematic evolution of CSII research. The findings also offer practical implications for marketing strategies, particularly in leveraging social influence, digital trust, and consumer engagement within online platforms. Future research is encouraged to expand data sources and integrate complementary analytical approaches to enrich the understanding of CSII across diverse contexts.